Diego de TORRES VILLARROEL, «Teatro breve I (Obra profana)», Epicteto Díaz Navarro y Fernando Doménech Rico (eds.). Madrid, Iberoamericana/Vervuert, 2012, 442 págs. - Rivero Machina, Antonio (Cuadernos de Estudios del Siglo XVIII, 2012)
SIN RESUMEN